PERAN FINANCIAL TECHNOLOGY (FINTECH) DALAM MEMBANTU PERKEMBANGAN WIRAUSAHA UMKM - Ningsih, Diah Rahayu (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— The development of technology and information attract various products to the community. Fintech or Financial Technology is one of the brave services that currently helps many people. This technology is engaged in the financial and economic industries. Various types of Fintech exist to help financial and entrepreneurial problems in society. Systems and services that are easy and fast, make Fintech increasingly in demand. This research and scientific study aims to analyze and understand the role of Fintech in assisting the development of Micro, Small and Medium Enterprises. It cannot be denied that capital and financial problems are the main problems in entrepreneurial activities. Capital lending system that is done through banks is fairly difficult, Micro, Small and Medium Enterprises issued generally do not have business completeness such as financial statements. Therefore, Fintech tries to offer a capital loan system that is easier and faster. Interestingly, this Fintech system continues to increase in terms of demand. Related, it is interesting to discuss in order to understand the role and successful thinking in order to improve Fintech to support Micro, Small and Medium Enterprises efforts. Keywords— Fintech, Entrepreneurship, Micro, Small and Medium Enterprises (UMKM), Capital Abstrak— Perkembangan teknologi dan informasi menghadirkan berbagai produk layanan untuk masyarakat. Fintech atau Financial Technology menjadi salah satu layanan daring yang saat ini banyak membantu masyarakat. Teknologi ini bergerak dalam industri keuangan dan ekonomi. Berbagai jenis Fintech hadir untuk membantu masalah keuangan dan kewirausahaan masyarakat. Sistem dan layanan yang mudah dan cepat, membuat Fintech semakin diminati. Penelitian dan kajian ilmiah ini bertujuan untuk menganlisis dan mengetahui peran Fintech dalam membantu perkembangan wirausaha Usaha Mikro, Kecil, dan Menengah. Tidak dapat dipungkiri bahwa masalah permodalan dan keuangan menjadi masalah utama dalam kegiatan wirausaha. Sistem peminjaman modal yang dilakukan melalui bank terbilang sulit, apalagi UMKM yang pada umumnya tidak memiliki kelengkapan usaha seperti laporan keuangan. Karena itu, Fintech mencoba untuk menawarkan sistem peminjaman modal yang lebih mudah dan cepat. Menariknya, sistem Fintech ini terus mengalami peningkatan dari segi permintaan. Sehingga, hal tersebut menarik untuk diamati guna mengetahui peran dan dampak yang berhasil dari munculnya Fintech bagi pelaku usaha UMKM.  Kata Kunci— Fintech, Wirausaha, Usaha Mikro, Kecil, dan Menengah (UMKM), Modal